Silicon transport and its “homeostasis” in rice - Sheng Huang; Jian Feng Ma (Quantitative Plant Biology)
Silicon (Si), the most abundant mineral element in soil, functions as a beneficial element for plant growth. Higher Si accumulation in the shoots is required for high and stable production of rice, a typical Si-accumulating plant species. During the last two decades, great progresses has been made in the identification of Si transporters involved in uptake, xylem loading and unloading as well as preferential distribution and deposition of Si in rice. In addition to these transporters, simulation by mathematical models revealed several other key factors required for efficient uptake and distribution of Si. The expression of Lsi1, Lsi2 and Lsi3 genes is down-regulated by Si deposition in the shoots rather than in the roots, but the exact mechanisms underlying this down-regulation are still unknown. In this short review, we focus on Si transporters identified in rice and discuss how rice optimizes Si accumulation (“homeostasis”) through regulating Si transporters in response to the fluctuations of this element in the soil solution.